E-GOVERNMENT EFFECTIVENESS IN COMBATING CORRUPTION AND IMPROVING PUBLIC SERVICES - Wendra Afriana; Harmawan Susetiyana; Oktarina Putri; Harry Azis (Department of Governmental Science FISIP UNPAD, 2020)
The government's step to be able to fight corruption is not just a discourse. One effort that has been made in e-government. E-government is a model of government system that utilizes information technology in providing information and services for its citizens. The aim is to create good governance that is free from corruption so that it has an impact on better quality public services. Some research shows e-government can reduce corruption and improve public service delivery through transparency and accountability by considering the type of corruption. This research uses qualitative methods and descriptive. Data collection techniques used are literature, such as books, articles and research results relating to e-government in Indonesia and other countries in combating corruption. The results showed, first, the successful implementation of e-government to reduce corruption was highly dependent on the state of the country's political economy. While in an economic perspective, the success of e-government depends on the country's information and communication technology (ICT) infrastructure, one of which is the level of internet penetration. Second, e-government is considered not always effective in reducing various types of corruption. for minor corruption, the application of e-government is considered effective. Meanwhile, for major corruption, such as irregularities in the use of budget and mega corruption involving politicians, it is more difficult to deal with just implementing e-government.